Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/elps.201200463
|View full text |Cite
|
Sign up to set email alerts
|

Determination of electrokinetic and hydrodynamic parameters of proteins by modeling their electrophoretic mobilities through the electrically charged spherical soft particle

Abstract: This work explores the possibility of using the electrically charged "spherical soft particle" (SSP) to model the electrophoretic mobility of proteins in the low charge regime. The general framework concerning the electrophoretic mobility of the SSP already presented in the literature is analyzed and discussed here in particular for polyampholyte-polypeptide chains. In this regard, this theory is applied to BSA for different protocol pH values. The physicochemical conditions required to model proteins as SSP f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 61 publications
(209 reference statements)
1
21
0
Order By: Relevance
“…In these regards, SSP electrophoretic mobility models presented by Ohshima for the low charge regime are useful, where the particle core is present and the flow of the BGE solution in the polyampholyte layer is allowed. In , we study the electrophoretic mobility of BSA through the SSP model for different pH values to visualize this protein denaturation in the presence of a particle core. In this regard, it must be observed that experimentally measured mobilities of proteins are necessary for the determination of their electrokinetic and hydrodynamic parameters.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In these regards, SSP electrophoretic mobility models presented by Ohshima for the low charge regime are useful, where the particle core is present and the flow of the BGE solution in the polyampholyte layer is allowed. In , we study the electrophoretic mobility of BSA through the SSP model for different pH values to visualize this protein denaturation in the presence of a particle core. In this regard, it must be observed that experimentally measured mobilities of proteins are necessary for the determination of their electrokinetic and hydrodynamic parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the use of SPP is an appropriate starting point to model a protein electrophoretic mobility within the wider framework of the SSP, allowing, in principle, to assign a polypeptide hydration uniformly distributed in the whole particle. We present the application of the SSP to the modeling of electrophoretic mobility of polypeptides in .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations